Formulación de proyectos sociales y atributos para el liderazgo. Miradas desde dirigentes sociales chilenos - Marcelo Andrés Gallegos Fuentes; Carmen Gloria Jarpa; Sady David Alejandro Leaman Hasbún; Héctor Agustín Vargas Muñoz (Eleuthera)
The study aims to describe the appreciations that Chilean social leaders attribute to three relevant dimensions for the formulation and implementation of social projects (knowledge, the community, and the involved agents). Additionally, it seeks to identify the attributes that they consider relevant for exercising leadership in these types of initiatives. The participating collective consists of 741 social leaders from the Ñuble Region, located in the central-southern territory of Chile. This is a quantitative study with a descriptive scope. The information was gathered through an ad hoc survey.The results demonstrate a high appreciation in the dimension of conceptual, procedural, and practical knowledge. In the community participation dimension, there is appreciation at all levels (informative, participative, collaborative, and committed). In the dimension of the involved agents, the appreciation is expressed in a descending order (State, community, municipality, experts, and private enterprises). Regarding the attributes considered relevant for exercising leadership, those of a democratic nature stand out, such as respect for opinions and the establishment of dialogue to reach agreements. Finally, the need to conduct studies that address, from a qualitative perspective, the attributes that leaders consider relevant for the exercise of leadership is evidenced.